PENGARUH ATRIBUT SUPERMARKET TERHADAP KEPUASAN KONSUMEN (STUDI KASUS SUPERMARKET X DI KOTA PADANG) - Siska Lusia Putri, Mohammad Abdilla, Sari Octavera (LPPM Universitas Muhammadiyah Sumatera Barat, 2016)
The purpose of this study was to to analyze how the supermarket attributes influence on consumer satisfaction in the Supermarket X. Supermarket attributes that studied were merchandise, product, atmosphere, personnel, price, and convenience in the supermarket.The object of research was consumers who shopped at the supermarket X. This research was descriptive quantitative attribute that described the influence of the supermarket with customer satisfaction using regression analysis and correlation. The study design used was cross sectional with a single method of sampling non probability sampling. The results of this study indicated that the attribute of Supermarket X includes merchandise, product, price, and convenience in-store positive and significant impact on customer satisfaction. While the other X Supermarket attribute the atmosphere and personnel and no significant positive effect on customer satisfaction. Supermarket attribute coefficient value X respectively were as follows: First, the price X5 attribute with a value at 6.800. This coefficient value was high compared to most other supermarket attributes. Second, the product X2 attribute with a value amounted to 3.826. Third, the X6 attribute comfort in-store with a value at 3.687. Fourth, the merchandise X1 attribute with a value amounted to 3.687. Fifth, namely personnel X4 attribute with a value at 0.149. Lastly, the atmosphere X3 attribute with a value at 0.025. Supermarket attribute X (merchandise, product, atmosphere, personnel, price, and convenience in-store) were simultaneously positive and significant impact on consumer satisfaction in Supermarket X. The value of adjusted R Square Supermarket attributes of X by 0.874. Keywords: attribute of supermarket, merchandise, product, atmosphere, personnel, price, convenience, customer satisfaction, Supermarket X